Integrated Transcriptomics and Widely Targeted Metabolomics Analyses Provide Insights Into Flavonoid Biosynthesis in the Rhizomes of Golden Buckwheat (Fagopyrum cymosum) - Huang, Juan; Wang, Luyuan; Tang, Bin; Ren, Rongrong; Shi, Taoxiong; Zhu, Liwei; Deng, Jiao; Liang, Chenggang; Wang, Yan; Chen, Qingfu (Frontiers in Plant Science, 2022)
Golden buckwheat (Fagopyrum Cymosum) is a traditional Chinese medicine and is getting more attention because of its high value of various medicinal and nutritional metabolites, especially flavonoids (catechin and epicatechin). However, the metabolites as well as their encoding genes in golden buckwheat have not been identified in the global landscape yet. This study performed transcriptomics and wide targeted metabolomics analyses for the first time in the rhizomes of golden buckwheat. As a result, 10,191 DEGs and 297 DRMs were identified, among which the flavonoid biosynthesis pathway was enriched in both transcriptome and metabolome. The integration analyses of the transcriptome and metabolome revealed a network related to catechin, in which four metabolites and 14 genes were interacted with each other. Subsequently, a SG5 R2R3-MYB transcription factor, named as FcMYB1, was identified as a transcriptional activator in catechin biosynthesis, as it was positively correlated to eight flavonoid biosynthesis genes in their expression patterns and directly binding to the promoters of FcLAR2and FcF3'H1 by yeast one hybrid analysis. Finally, a flavonoid biosynthesis pathway was proposed in the rhizomes of golden buckwheat, including 13 metabolites, 11 genes encoding 9 enzymes, and one MYB transcription factor. The expression of 12 DEGs was validated by qRT-PCR, resulting in a good agreement with the Pearson R ranging from 0.83 to 1. The study provided a comprehensive flavonoid biosynthesis and regulatory network of golden buckwheat.